2017
DOI: 10.3390/rs9100990
|View full text |Cite
|
Sign up to set email alerts
|

A Rigorously-Weighted Spatiotemporal Fusion Model with Uncertainty Analysis

Abstract: Abstract:Interest has been growing with regard to the use of remote sensing data characterized by a fine spatial resolution and frequent coverage for the monitoring of land surface dynamics. However, current satellite sensors are fundamentally limited by a trade-off between their spatial and temporal resolutions. Spatiotemporal fusion thus provides a feasible solution to overcome this limitation, and many blending algorithms have been developed. Among them, the popular spatial and temporal adaptive reflectance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…A technical challenge is that the usability of fine spatial-resolution images (e.g., Landsat and Sentinel-2 images) are still largely constrained by their low revisit frequency and cloud contamination. Developing advanced methods for fusing satellite images from high-temporal frequency (e.g., MODIS) and fine spatial-resolution sensors (e.g., Landsat Operational Land Imager or Sentinel-2 Multispectral Imager) has become a well-established research field [1][2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A technical challenge is that the usability of fine spatial-resolution images (e.g., Landsat and Sentinel-2 images) are still largely constrained by their low revisit frequency and cloud contamination. Developing advanced methods for fusing satellite images from high-temporal frequency (e.g., MODIS) and fine spatial-resolution sensors (e.g., Landsat Operational Land Imager or Sentinel-2 Multispectral Imager) has become a well-established research field [1][2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…A number of satellite image fusion methods have been developed to predict synthetic Landsat-like images from dense time series of MODIS images and a limited set of fine-resolution Landsat images. Examples include the Spatial and Temporal Adaptive Reflectance Fusion Model (STARFM) [1], the Enhanced version of STARFM (ESTARFM) [2], the Spatial Temporal Adaptive Algorithm for Mapping Reflectance Change (STAARCH) [3], the Unmixing-based Spatial-Temporal Reflectance Fusion Model (U-STFM) [4,5], the Flexible Spatiotemporal Data Fusion (FSDAF) model [6], the Spatiotemporal image-fusion model (STI-FM) for enhancing the temporal resolution [7], the Hybrid Color Mapping (HCM) approach [8], the Rigorously-Weighted Spatiotemporal Data Fusion Model (RWSTFM) [9], the Prediction Smooth Reflectance Fusion Model (PSRFM) [10]. These studies have demonstrated that the fusion methods are mostly limited to predicting spectral changes in reflectance due to gradual vegetation phenological changes [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, a number of image fusion methods have been developed to predict synthetic Landsat-like images from frequent MODIS images and a limited set of Landsat images. Examples include the Spatial and Temporal Adaptive Reflectance Fusion Model (STARFM) [1], the Enhanced version of STARFM (ESTARFM) [2], the Spatial Temporal Adaptive Algorithm for Mapping Reflectance Change (STAARCH) [3], the Unmixing-based Spatial-Temporal Reflectance Fusion Model (U-STFM) [4,5], the Flexible Spatiotemporal Data Fusion (FSDAF) model [6], the Spatiotemporal image-fusion model (STI-FM) for enhancing the temporal resolution [7], the Hybrid Color Mapping (HCM) Approach [8] and the Rigorously-Weighted Spatiotemporal Data Fusion Model (RWSTFM) [9] and so forth. However, studies have demonstrated that all of the above reflectance fusion methods have their advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have demonstrated that all of the above reflectance fusion methods have their advantages and disadvantages. Some of them are only effective or applicable for certain applications [1][2][3][4][5][6][7][8][9]. Interested readers can find concise reviews for these methods in [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation